Local Identities in Late Medieval and Early Modern England - Woolf, Daniel. author. aut Link
XVII, 256 p.
Keywords: Inspired by the path-breaking work of Robert Tittler, the authors explore late Medieval and Early Modern community and identity across England. They examine the decline of neighbourliness, the politics of market towns, clerical status, charity, crime, and ways in which overlapping communities of court and country, London and Lancashire, relate.